2020
DOI: 10.1016/j.amjcard.2020.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Prevalence and Risk Factors for Cognitive Decline and Improvement After Transcatheter Aortic Valve Implantation

Abstract: Changes to cognition, both decline and improvement, are commonly reported after transcatheter aortic valve implantation (TAVI). However, previous systematic reviews and metaanalyses have missed these subgroups by assessing whole-group-averages for cognitive outcomes. We sought to pool estimates to identify the prevalence of cognitive decline and improvement after TAVI, as well as associated factors for these outcomes. A systematic review identified 15 articles appropriate for meta-analysis. When robust cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 30 publications
0
30
0
2
Order By: Relevance
“… 29 Baseline cognitive impairment was the only factor associated with post-TAVI cognitive improvement. 29 The use of EPD and early mobilization have been also associated with reduction in post-operative delirium—a predictor of cognitive impairment and reduced long-term survival. 7 , 30 …”
Section: Cognitive Declinementioning
confidence: 91%
See 1 more Smart Citation
“… 29 Baseline cognitive impairment was the only factor associated with post-TAVI cognitive improvement. 29 The use of EPD and early mobilization have been also associated with reduction in post-operative delirium—a predictor of cognitive impairment and reduced long-term survival. 7 , 30 …”
Section: Cognitive Declinementioning
confidence: 91%
“… 28 When assessing cognitive function more robustly approximately equivalent numbers of TAVI patients experience cognitive decline and cognitive improvement, which gives rise to the null findings (preservation of cognitive function) using a whole-group-analysis approach (cognitive decline in 14% and improvement in 19% within 6 months after TAVI). 29 …”
Section: Cognitive Declinementioning
confidence: 99%
“…In older individuals delirium is associated with a range of poor outcomes including functional decline, loss of independence, cognitive decline and dementia, institutionalization and death ( 13 , 14 ). Furthermore, another meta-analysis by our group demonstrated that cognitive decline is seen in up to 14% of patients in the year following TAVI ( 11 ). Cognitive decline can lead to clinically significant cognitive impairments including mild cognitive impairment (MCI) and dementia ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there are no risk prediction models for post-procedural cognitive decline in TAVI patients or cardiac patients generally. A recent meta-analysis ( 11 ) reported that the use of cerebral embolic protection devices and pre-procedure cognitive impairment reduced the risk of post-TAVI cognitive decline. Within the context of an aging population, there is a general rising demand for pre-operative risk stratification of older adults to aid informed consent and the guiding of patient expectations ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation